Analisis Penilaian Kondisi Keuangan Pada Pemerintah Kabupaten Magelang Periode Tahun 2015-2019 - Nuwun Priyono; Risma Wira Bharata; Ari Nurul Fatimah (ITB AAS INDONESIA, 2021)
This study aims to analyze and assess trends in the financial condition of the Government of Magelang Regency which includes: financial factors and environmental factors. This study uses secondary data. The data analyzed includes data on financial reports in the Magelang Regency Government such as: balance sheet, APBD, budget realization reports, and operational reports. The analysis year period starts from 2015-2019. Analysis of the financial condition assessment using the Fiscal Tren Monitoring System (FTMS) model in the Magelang Regency Government. The research method used in this research is to use a descriptive approach based on secondary data processing and coupled with numerical analysis. The analysis technique in this research uses descriptive statistics, namely: presenting data in the form of tables, graphs, averages and percentage calculations. Analysis of the financial condition assessment using the FTMS model in Magelang Regency 2015-2019 shows that the financial factor includes 4 indicators consisting of 9 sub indicators. Of the 9 financial sub indicators, 5 sub indicators have the expected trend and 4 sub indicators have an unexpected trend. Furthermore, environmental factors consist of 1 indicator which includes 5 sub indicators. Of the 5 sub indicators, 2 sub indicators have the expected trend and 3 sub indicators have less expected trends for the assessment of the financial condition of the Magelang Regency government.